DINAMIKA PENALARAN MORAL REMAJA YANG MENGIKUTI MENTORING AGAMA ISLAM DI KOTA BANDA ACEH - Vera Nova; Ida Fitria; M Reza Rifki (State Islamic University (UIN) Ar-Raniry, 2020)
This study aims to determine the dynamics of moral reasoning among adolescents who take part in the Islamic mentoring program in Banda Aceh. This study used a case study qualitative approach involving six research subjects from 3 high schools in Banda Aceh who had participated in Islamic mentoring for more than one year. The data collection methods used was interviews, observation and FGD. The data analysis used is thematic analysis. The results of this study shows that the moral reasoning of six research subjects has been at the level of post conventional moral reasoning, social contract orientation stage of legality and moral orientation with universal ethical principles. Dynamic moral reasoning in the six subjects is formed from several factors, namely religious education from parents, religious education in schools especially the mentoring programs, curriculum and mentoring implementation methods, length of time for implementing mentoring, mentoring environment, and continuity of mentoring or length of time following mentoring.